Features Of the Development of Physical Abilities Law Enforcement Staff - Gapparov Khafiz Zakhidovich; Hikmatilla Rakhmanberdievich Akhmedov (Genius Journals, 2022)
the article deals with the issues of physical training of law enforcement officers. It is an integral part of the professional training of law enforcement officers, aimed not only at improving the basic physical abilities (endurance, strength, speed, dexterity, etc.), but also at performing professional motor actions.
Keywords: physical training; physical abilities; law enforcement agencies